A tunable fast filter bank - Liu, Qing Lai (2015)
Fast filter bank (FFB) derived from frequency response masking (FRM) technique has good frequency selectivity and very low computational complexity. This final year project proposes a feasible method to design a FFB with tunable passband width. In the proposed method, a set of fixed predesigned half-band filters, each of which covers a very small part of tunable range, are implemented as first level prototype filters. It is demonstrated that if the second level prototype filter is replaced by a half-band filter with sharp transition band designed using FRM technique, the tunable range will improve significantly, meanwhile, having an overall low complexity. The proposed tunable FFB has a simple updating process when tuning the passband width. It is shown that the proposed method has an overall very low complexity when operating in a moderate tunable range. A set of equations is also derived to simplify the design process.